1998
DOI: 10.1590/s0103-84781998000300018
|View full text |Cite
|
Sign up to set email alerts
|

Efeito dos fungos entomopatogenicos Metarhizium anisopliae e Beauveria bassiana em ovos de Rhipicephalus sanguineus (acarlixodidae)

Abstract: Este experimento foi conduzido para conhecer os efeitos de duas espécies de fungos, Beauveria bassiana e Metarhizium anisopliae em ovos do carrapato Rhipicephalus sanguineus sob temperatura e umidade constantes (27 ± 1° C e > 80% de umidade relativa (UR)) e variáveis (25 ±5° C e > 60% UR). Ovos de R. sanguineus foram imersos em quatro concentrações (10(8), 10(7), 10(6) e 10(5) conídios/ml) de dois isolados de B. bassiana (Bb 986 e Bb 747) e três isolados de M. anisopliae ( Ma 959, Ma E9 e Ma 319). Os per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 2 publications
1
2
0
2
Order By: Relevance
“…Previous studies have shown that B. bassiana and M. anisopliae have great potential as biological control agents for different arthropod species 5,6 . In the current study, C. felis felis eggs exposed to Bb747 at 10 8 conidia mL −1 had low hatchability after 36 h compared to controls, while those exposed to Bb986 showed low hatchability after 48 h (Table 1).…”
Section: Resultssupporting
confidence: 47%
“…Previous studies have shown that B. bassiana and M. anisopliae have great potential as biological control agents for different arthropod species 5,6 . In the current study, C. felis felis eggs exposed to Bb747 at 10 8 conidia mL −1 had low hatchability after 36 h compared to controls, while those exposed to Bb986 showed low hatchability after 48 h (Table 1).…”
Section: Resultssupporting
confidence: 47%
“…However, the ability of B. microplus to develop resistance to acaricides, consumer's demands for chemical free foods, and the negative environmental effects of acaricides call for the development of alternative strategies (Kay and Kamp 1994). Therefore, alternative methods for tick control, such as biological control using filamentous fungi, chiefly, M. anisopliae (Correia et al 1998;Kaaya and Hassan 2000) and Beauveria bassiana (Monteiro et al 1998b), have been pursued.…”
Section: Introductionmentioning
confidence: 99%
“…However, engorged R. microplus and R. sanguineus females were more susceptible to entomopathogenic fungi in comparison to H. excavatum females (Gindin et al, 2003). Further, 100% susceptibility of eggs to fungi were also reported (Gorshkova, 1966;Monteiro et al, 1998;Kaaya, 2000). Elham et al (2013) studied the effect of Scopulariopsis brevicaulis fungal spore suspension and culture filtrate on larvae, nymphs and adults of H. anatolicum and high mortality of larvae and reduced biotic potential of the adults was reported.…”
Section: Biological Controlmentioning
confidence: 99%